Morphological characterization of maize (Zea mays L.) genotypes for drought tolerance - Tasnim, Fariha; Ahmed, Md. Sultan; Rahaman, Md. Arifur; Sagor, G. H. M. (Journal of Phytology, 2025)
Drought stress poses a major challenge to global maize (Zea mays L.) production, significantly affecting food security. This study aimed to identify drought-tolerant maize genotypes by evaluating their morphological characteristics under controlled and field conditions. Morphological traits, such as shoot and root length in the seedling stage and plant height, canopy temperature, ear length, and kernel weight at vegetative and reproductive stages, were analyzed under drought stress conditions induced by PEG and reduced field capacity. Significant genetic variability was observed among the genotypes for most traits, with phenotypic coefficient of variation (PCV) consistently higher than genotypic coefficient of variation (GCV). Heritability estimates ranged from 37% to 99.82%, with traits such as plant height, kernel weight per ear, ear weight, hundred-seed weight, and yield per pot demonstrating both high heritability and genetic advance. Yield showed positive correlations with plant height, ear length, ear diameter, kernel number per row, and kernel weight per ear, while negatively correlating with days to ear moisture loss. Principal Component Analysis (PCA) revealed that the first five components explained 83.46% of the total variation, with yield-related traits contributing most to the variation. Cluster analysis revealed eight distinct groups at the seedling stage and six at the vegetative and reproductive stages, with genotypes in Clusters 5 and 6 exhibiting superior drought tolerance, particularly in traits like root number, kernel number per ear, and kernel weight per ear. This study identified BHM-7, BHM-14, and BHM-15 as genotypes with superior drought tolerance at the reproductive stage, while Black, Violet, and White Vutta showed resilience at the seedling stage, exhibiting greater plant vigor under drought stress. Recognizing these genotypes as a significant step toward breeding drought-resistant maize varieties, contributing to food security and sustainable agriculture.